2021
DOI: 10.3390/ijms22063147
|View full text |Cite
|
Sign up to set email alerts
|

Putative LysM Effectors Contribute to Fungal Lifestyle

Abstract: Fungal LysM effector proteins can dampen plant host–defence responses, protecting hyphae from plant chitinases, but little is known on these effectors from nonpathogenic fungal endophytes. We found four putative LysM effectors in the genome of the endophytic nematophagous fungus Pochonia chlamydosporia (Pc123). All four genes encoding putative LysM effectors are expressed constitutively by the fungus. Additionally, the gene encoding Lys1—the smallest one—is the most expressed in banana roots colonised by the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…The LysM-containing effectors, such as Slp1 in Magnaporthe oryzae, ChELP1 and ChELP2 in Colletotrichum higginsianum, Vd2LysM in Verticillium dahliae, RsLysM in Rhizoctonia solani, Mgx1LysM in Zymoseptoria tritici, had been proved to contribute to virulence by disturbing the activation of chitin-triggered immunity (Mentlak et al, 2012;Takahara et al, 2016;Kombrink et al, 2017;Dolfors et al, 2019;Tian et al, 2021). The evolutionary study from 57 endophytes and fungi with diverse lifestyles showed that LysM effectors contributed to fungal lifestyle (Suarez-Fernandez et al, 2021). Additionally, RiSLM, a secreted LysM effector from arbuscular mycorrhiza (AM) fungal species Rhizophagus irregularis, protected fungal cell walls from chitinase by binding to chitin oligosaccharides and effectively interfere with chitin-triggered immune response to subvert chitintriggered immunity during symbiosis (Gust et al, 2012;Zeng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The LysM-containing effectors, such as Slp1 in Magnaporthe oryzae, ChELP1 and ChELP2 in Colletotrichum higginsianum, Vd2LysM in Verticillium dahliae, RsLysM in Rhizoctonia solani, Mgx1LysM in Zymoseptoria tritici, had been proved to contribute to virulence by disturbing the activation of chitin-triggered immunity (Mentlak et al, 2012;Takahara et al, 2016;Kombrink et al, 2017;Dolfors et al, 2019;Tian et al, 2021). The evolutionary study from 57 endophytes and fungi with diverse lifestyles showed that LysM effectors contributed to fungal lifestyle (Suarez-Fernandez et al, 2021). Additionally, RiSLM, a secreted LysM effector from arbuscular mycorrhiza (AM) fungal species Rhizophagus irregularis, protected fungal cell walls from chitinase by binding to chitin oligosaccharides and effectively interfere with chitin-triggered immune response to subvert chitintriggered immunity during symbiosis (Gust et al, 2012;Zeng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“… 2020 , Suarez-Fernandez et al . 2021 ). Findings like these indicate that effectors are not (plant) symbiont-specific inventions to mediate (plant) host colonization, but should rather be seen as molecules that are secreted by fungi in order to manipulate their environment to their benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate effector proteins have also been found in the genomes of fungi from all lifestyles, including saprotrophic fungi [ 11 , 12 ]. Likewise, it was originally assumed that effectors were fast-evolving genes with minimal homology across species, however, the increased availability of sequenced fungal genomes has shown conservation of some of these sequences across a broader range of fungi than expected [ 5 , 11 , 13 , 14 ]. While candidate effectors are more abundant in biotrophic fungi [ 4 ], the genomic content and evolution of these effectors are more likely to be influenced by lineage than lifestyle [ 2 ].…”
Section: Introductionmentioning
confidence: 99%